Progress in doping and crystal deformation for polyanions cathode based lithium-ion batteries - Sajeela Awasthi; Srikanta Moharana; Vaneet Kumar; Nannan Wang; Elham Chmanehpour; Anupam Deep Sharma; Santosh K. Tiwari; Vijay Kumar; Yogendra Kumar Mishra (Nano Materials Science)
Polyanion-based materials are considered one of the most attractive and promising cathode materials for lithium-ion batteries (LIBs) due to their good stability, safety, cost-effectiveness, suitable voltages, and minimal environmental impact. However, these materials suffer from poor rate capability and low-temperature performance owing to limited electronic and ionic conductivity, which restricts their practical applicability. Recent developments, such as coating material particles with carbon or a conductive polymer, crystal deformation through the doping of foreign metal ions, and the production of nanostructured materials, have significantly enhanced the electrochemical performances of these materials. The successful applications of polyanion-based materials, especially in lithium-ion batteries, have been extensively reported. This comprehensive review discusses the current progress in crystal deformation in polyanion-based cathode materials, including phosphates, fluorophosphates, pyrophosphates, borates, silicates, sulfates, fluorosilicates, and oxalates. Therefore, this review provides detailed discussions on their synthesis strategies, electrochemical performance, and the doping of various ions.